Synthesis and Antiproliferative Activity of Novel Imipridone-Ferrocene Hybrids with Triazole and Alkyne Linkers - Tamás Czuczi; József Murányi; Péter Bárány; István Móra; Adina Borbély; Miklós Csala; Antal Csámpai (MDPI AG, 2022)
Imipridones, including ONC201, ONC206 and ONC212 (which are emblematic members of this class of compounds developed by Oncoceutics) constitute a novel class of anticancer agents, with promising results in clinical trials. With the aim of increasing the ROS (reactive oxygen species) responsivity of the synthesized molecules, a set of novel ferrocene-imipridone hybrids were designed and synthesized. Our strategy was motivated by the documented interplay between the imipridone-triggered activation of TRAIL (the tumor necrosis factor-related apoptosis-inducing ligand) and mitochondrial ClpP (Caseinolytic protease P) and the ROS-mediated effect of ferrocene-containing compounds. In order to obtain novel hybrids with multitarget characters, the ferrocene moiety was tethered to the imipridone scaffold through ethynylene and 1,2,3-triazolyl linkers by using Sonogashira coupling of Cu(I)- and Ru(II)-catalyzed azide-alkyne cycloadditions. The biological activities of the new hybrids were examined by using in vitro cell viability assays on four malignant cell lines (PANC-1, A2058, EBC-1 and Fadu), along with colony formation assays on the most resistant PANC-1 cell line. Several hybrids caused a significantly greater drop in the cell viability compared to ONC201, and two of them completely overcame the resistance, with IC50 values comparable to those produced by ONC201. The two most potent hybrids, but not ONC201, induced apoptosis/necrosis in PANC-1 and A2058 cells after 24 h of treatment.